Pengaruh Produk dan Harga terhadap Minat Beli Konsumen CV Pesona Elok Wiyung Surabaya: - Bagus Rachmatri Landaru; Ety Dwi Susanti (LPPM Institut Nasional Laa Roiba Bogor, 2023)
In this study has the aim of obtaining information about the effect of products and prices on consumer buying interest simultaneously and partially. The approach used is a quantitative approach. The data collection technique used is using a sample with probability sampling technique and the technique in collecting data is using a questionnaire on google form. The measurement scale in this study is the Likert scale 5-1. In addition, when analyzing the data, the researcher used multiple linear regression analysis using the SPSS program. Respondents in this study found 100 consumers of CV Pesona Elok Wiyung Surabaya (MS Glow by Elok Nabila Official Central Distributor). The results obtained in this research indicate that partially there is a significant influence on the independent variables of this research, namely Product and Price on consumer buying interest. In addition, at the same time, it was found that there was a significant effect on all variables on consumer buying interest at CV Pesona Elok Wiyung Surabaya (MS Glow by Elok Nabila, Central Authorized Distributor). Keyword: Product; Prices; consumer buying interest